(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Technology is used in remote patient monitoring (RPM) to keep track of patients’ health statuses and vital signs away from the usual healthcare settings. Healthcare professionals can remotely gather real-time data on patients’ physiological characteristics, medication adherence, and other pertinent health data by using connected devices, such as wearable’s, sensors, and mobile applications. Healthcare delivery could change dramatically with the help of remote patient monitoring and smart healthcare support. Utilizing technology, healthcare professionals may proactively monitor patients, personalize care, and enhance health outcomes. In order to fully utilize the potential of this strategy and revolutionize healthcare for the benefit of patients everywhere, it will be essential to overcome the implementation-related hurdles. The aim of this paper is to examine the latest advancements in smart healthcare systems, specifically focusing on wearable and smartphone devices for health monitoring, as well as the application of machine learning for disease diagnosis, and assistive frameworks like social robots developed for the ambient assisted living environment. Furthermore, the study emphasizes software integration designs that are crucial for establishing smart healthcare systems by seamlessly incorporating the advantages of data analytics and other AI tools.